Elaboration and characterization of engineered floors made with woods of different densities - Barrera Cruz, Omar Isaí; Rodríguez Anda, Raúl; Silva Guzmán, José Antonio; Fuentes Talavera, Francisco Javier (Instituto de Ecología, A.C., 2023)
A possible option to increase the value of low-density woods may be to combine species with different densities. The manufacture of boards involving joining and mixing wood with different properties is known as an engineering product. The present work aimed to design, produce, and evaluate a 16 mm-thick three-layer engineered floor using coconut palm (Cocos nucifera) or melina (Gmelina arborea) as substrate and reinforced with red oak (Quercus castanea) using three types of adhesives: urea formaldehyde, henkel loctite and soy furfural. The results, with both wood substrates, showed an average specific weight of 0.53 g cm-3 and an average moisture content of 9%. The flexural strength ranged from 12 MPa to 62 MPa and from 1346 MPa to 10 660 MPa in modulus of elasticity, the combination of oak-melina-oak with urea formaldehyde being the one that presented the best results. Brinell hardness exhibits strengths from 30 N mm-2 to 48 N mm-2 with the oak-palm-oak combination with loctite achieving the highest value. The shear resistance of the gluing line renged from 0.11 MPa to 3.46 MPa, with the oak-palm-oak with soya furfural, oak-palm-oak with urea formaldehyde, as well as oak-melina-oak urea formaldehyde combinations showing no statistical differences. In delamination, floors with urea formaldehyde and furfural soy are susceptible to delamination by direct contact with water and while being subjected to dry changes in relative humidity in the environment of 35% and 55%.